Program Keliling Kampung (Kelompok Peduli Lingkungan dan Mewujudkan UMKM Pasti Unggul) KKN Kolaboratif 236 Tegalgede - Shinta Ayu Agustin; Rahma Nurul Aeny; Riesma Rukmana; Dila Priastita Intan Parastuti; Munika Duwi Anindia; Ananda Dewi Ratih Budi Puspitasari; Marta Alviana Rizka; Astri Novi Amalia; Avita Khoirunnisa; Unik Muni’ah Zahiroh; Didi Teguh Dwi Santoso; Rezha Pratama Ensas; Abi Cahya Ramadhani; Umar Faruq; Edi Suprawadi; H.B.A Jayawardana (Universitas Maritim AMNI Semarang, 2023)
KKN or Kuliah Kerja Nyata is mandatory program held by college. KKN Kolaboratif is program organized by the Jember Regency government with 18 college. The work program carried out by KKN Kolaboratif 236 is based on the problems that exist in the Tegalgede, such as the low level of public awareness in managing inorganic waste, the high level of use of inorganic waste, and the lack of digital UMKM marketing. That program aims to make the public aware of the separation of inorganic waste so that it can be recycled again and to help introduce and market UMKM products for Tegalgede digitally. The activities waste sorting competition also invited WCDI (World Clean Up Day Indonesia) and BSI (Bank Sampah Induk) to discuss determining the category of inorganic waste to be contested and related to the process of evaluating and transporting the results of the competition. The results were 14 RTs took part in the competition. Another program, the creation of e-catalog in collaboration with 20 UMKM in Tegalgede to enter their data into the catalog. The implication of this community service activity is that it can help residents to understand more about inorganic waste and make easier to access UMKM.